Workspace analysis and design of large-scale cable-driven printing robot considering cable mass and mobile platform orientation. (November 2021) - Chawla, Ishan; Pathak, P.M.; Notash, Leila; Samantaray, A.K.; Li, Qingguo; Sharma, U.K.
Abstract: This paper proposes a methodology to determine the printable workspace of a cable robot by taking cable mass and mobile platform orientation into account. This workspace has a characteristic feature of avoiding the collision of lower cables with the previous layers of the structure during 3D printing while maintaining cable tensions inside the prescribed positive tension bounds. Since redundant robot is taken into consideration, the printable workspace possesses multiple solutions and hence, a unique solution needs to be selected based upon a selection criterion. Therefore, to select a unique solution, this paper proposes a selection criterion to minimize cable sagging and compares it with the conventional selection criterion of minimizing cable tension. For comparative analysis, various factors such as printable workspace, cable tensions and platform deflection of the robot are considered. The proposed selection criterion is further utilized to study the impact of variation in the geometric parameters on the printable workspace and the capacity margin of the robot. Finally, an optimal design is proposed using genetic algorithm for the desired printable workspace as well as constraint minimum capacity margin with an objective to minimize the installation space of the cable robot.